Optimization of a mass-rearing system to produce codling moth, Cydia pomonella, for a Sterile Insect Release programme in South Africa - Stenekamp, Daleen (Stellenbosch : University of Stellenbosch, 2011)
Thesis (PhD (Conservation Ecology and Entomology))--University of Stellenbosch, 2011.